2008
DOI: 10.1021/jm701445q
|View full text |Cite
|
Sign up to set email alerts
|

Ring Size in Octreotide Amide Modulates Differently Agonist versus Antagonist Binding Affinity and Selectivity

Abstract: H-DPhe 2 -c[Cys 3 -Phe 7 -DTrp 8 -Lys 9 -Thr 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Third, the selective sst 1 (S-406-062) or sst 4 (S-315-297) agonist (17,19) injected under the same conditions showed a trend toward decrease in water intake. In line with these findings, previous reports showed that the stable sst agonist octreotide, which is devoid of sst 1 and sst 4 affinity, while binding to sst 2 Ͼ sst 5 ϾϾ sst 3 (28), increased water consumption within the first 10 min after intracerebroventricular injection in picomolar range in rats that had no access to food (30).…”
Section: Discussionsupporting
confidence: 82%
“…Third, the selective sst 1 (S-406-062) or sst 4 (S-315-297) agonist (17,19) injected under the same conditions showed a trend toward decrease in water intake. In line with these findings, previous reports showed that the stable sst agonist octreotide, which is devoid of sst 1 and sst 4 affinity, while binding to sst 2 Ͼ sst 5 ϾϾ sst 3 (28), increased water consumption within the first 10 min after intracerebroventricular injection in picomolar range in rats that had no access to food (30).…”
Section: Discussionsupporting
confidence: 82%
“…Octreotide is a clinically used SST like peptide drug. Compared with native SST-14, octreotide has used more stable D-Trp for L-Trp and the ring size has been decreased from 12 to 6 [76]. When maintaining the receptor binding affinity of somatostatin, octreotide has a prolonged plasma half-life of about 100 min in humans.…”
Section: Chemical Modification Of a Peptidementioning
confidence: 99%
“… Affinities are derived from competitive radioligand displacement assays in cells stably expressing the cloned human receptor using 125 I-[Leu 8 DTrp 22 Tyr 25 ]SRIF-28 (Cescato et al, 2008; Erchegyi et al, 2003; Erchegyi et al, 2008; Erchegyi et al, 2009; Grace et al, 2006; Grace et al, 2008) except for somatostatin-14 (Viollet et al, 1995) and somatostatin-28 (Viollet et al, 1995). …”
Section: Figurementioning
confidence: 99%